GATA-6 transcriptionally inhibits Shh to repress cell proliferation and migration in lung squamous cell carcinoma. (October 2019) - Xu, Linlin; Deng, Suyue; Xiong, Huanting; Shi, Wei; Luo, Shiwen; Chen, Limin
Highlights: GATA-6 is downregulated in LSCC. GATA-6 inhibits cell proliferation and migration of LSCC cells. GATA-6 transcriptionally represses Shh expression in LSCC. Shh rescues GATA-6-induced inhibition of LSCC cell proliferation and migration. Abstract: GATA-6 is a transcription factor that participates in cell lineage differentiation and organogenesis in many tissue types. The abnormal expression of GATA-6 is associated with the development of diverse cancers. GATA-6 acts as an oncogene or tumor suppressor based on tumor origin. Here, we investigated the effects of GATA-6 on lung squamous cell carcinoma (LSCC). We found that GATA-6 was significantly reduced in LSCC tissues compared with the paired normal tissues. The overexpression of GATA-6 inhibited LSCC cell proliferation and migration. Importantly, a luciferase reporter assay and chromatin immunoprecipitation assay demonstrated that GATA-6 negatively regulated the expression of sonic hedgehog (Shh) by directly binding to its promoter region. Furthermore, N-Shh stimulation rescued the inhibition of LSCC cell proliferation and migration upon GATA-6 overexpression. Thus, GATA-6 inhibited the proliferation and migration of LSCC cells by transcriptionally inhibiting the expression of Shh, indicating that targeting GATA-6 may be a potential approach for LSCC therapy.